PHYTOCHEMICAL IDENTIFICATION OF PELARGONIUM GRAVEOLENS L. AND STUDYING ITS BIOLOGICAL ACTIVITY - Suad. F. Dhifiar,; H. M. Habeeb, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to determine  the active compounds in alcoholic extracts (methanolic 75% and ethanolic 75%) of  Pelargonium gravolens leaves and flowers as well as their antibacterial and antioxidant  activities. The methanolic extract of dry leaves and fresh flowers (30 g each) gave  4.8650, 2.8015 g  respectively. While ethanolic extract for the same parts gave 5.5787, 2.1832g respectively.    Spectrophotometric analysis showed that, the flavonoids content in leaves and flowers methanol extract  were  20.38, 70.90 μg rutin equivalent/g of extract, respectively, as for ethanol  extract  those values were 21.89, 71.63 μg rutin equivalent/g of extract, respectively. According to the above findings,  it has been noticed that the flowers ethanol  extract  recorded the highest value for flavonoids (71.63 μg rutin equivalent /g of extract). The results indicate that the free radical scavenging activity ( RSA) of ethanolic extract of the flowers and leaves was lower than that of methanolic extract. Where the RSA percentages of  the leaves methanolic extract were (12, 13, 14, 16, 19 %) at a concentration (0.25, 0.50, 0.75, 1.00, 1.25 mg/ml) respectively, and for the flowers were (142, 162, 162) 164, 166%) at the same concentrations respectively.